(untitled) (Boletín de Políticas y Gestión Educativa, 2022)
Behind leadership there is a story not always in tune with education, but it is evident that there have been important advances, in particular for the effects it has on management that, otherwise, would be an exclusively instrumental and technical area. Today, different types of leadership have been incorporated that allow school organizations to have the options that are most appropriate to their realities, such as, for example, transformational, constructivist, inclusive leadership, and certainly distributed leadership that has been installed with force and has proven to be useful for school organizations.